Perceptions of Equine Assisted Activities and Therapies by Parents and Children with Spinal Muscular Atrophy - Lemke, Danielle (2014)
PURPOSE: To identify the physical and psychosocial effects of equine assisted activities and therapies (EAAT) on children with Spinal Muscular Atrophy (SMA) from the perspective of the child and their parents. METHODS: The families of all eligible children with SMA, who reported participation in EAAT, from a western metropolitan academic center were contacted and invited to participate. This study implemented qualitative, semi-structured interviews of children with SMA and their parents. RESULTS: Three themes emerged from the qualitative content analysis: physical/psychosocial benefits; relationship development with the horses, instructors, and children; and barriers to continued EAAT engagement. CONCLUSIONS: The data suggest the overall EAAT experience was a source of enjoyment, self-confidence, and normalcy for the children with SMA. The results of this study provide preliminary support for the use of EAAT among children with SMA.